2015
DOI: 10.1007/s12035-015-9423-8
|View full text |Cite|
|
Sign up to set email alerts
|

Tonic GABAA Receptors as Potential Target for the Treatment of Temporal Lobe Epilepsy

Abstract: Tonic GABAA receptors are a subpopulation of receptors that generate long-lasting inhibition and thereby control network excitability. In recent years, these receptors have been implicated in various neurological and psychiatric disorders, including Parkinson’s disease, schizophrenia, and epilepsy. Their distinct subunit composition and function, compared to phasic GABAA receptors, opens the possibility to specifically modulate network properties. In this review, the role of tonic GABAA receptors in epilepsy a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(28 citation statements)
references
References 138 publications
1
26
1
Order By: Relevance
“…Given the crucial role of inhibitory synapses in regulating both neuronal excitability and excitatory synaptic plasticity, changes in GABAergic synaptic efficacy can have important functional and pathological consequences [ 56 ]. As in excitatory neurotransmission, changes in GABA ( γ -aminobutyric acid) receptor composition, expression, cellular distribution, and function, therefore, have profound consequences for neural excitability, and they are associated with the etiology of several neurological and mental diseases, including epilepsy [ 57 ].…”
Section: Is the Gabaergic Synaptic Plasticity Implicated In The Epmentioning
confidence: 99%
“…Given the crucial role of inhibitory synapses in regulating both neuronal excitability and excitatory synaptic plasticity, changes in GABAergic synaptic efficacy can have important functional and pathological consequences [ 56 ]. As in excitatory neurotransmission, changes in GABA ( γ -aminobutyric acid) receptor composition, expression, cellular distribution, and function, therefore, have profound consequences for neural excitability, and they are associated with the etiology of several neurological and mental diseases, including epilepsy [ 57 ].…”
Section: Is the Gabaergic Synaptic Plasticity Implicated In The Epmentioning
confidence: 99%
“…Asynchronous GABA release, GABA spillover and tonic inhibition are known to modulate the input-output behavior of single neurons by shunting excitatory currents and hyperpolarizing the membrane potential and therefore have a protective role in epilepsy [ 46 , 47 ]. A decrease in tonic inhibition was identified in some animal models of epilepsy (see [ 48 , 49 ] for review), including Syn II KO and TKO mice [ 22 , 23 ]. The protective role of tonic inhibition from hyperexcitability is further strengthened by the tonic stimulation of presynaptic GABA B Rs by extracellular GABA.…”
Section: Discussionmentioning
confidence: 99%
“…In an earlier study we showed that quercetin has anticonvulsant activity in acute and chronic models of chemical kindling induced by pentylenetetrazole (PTZ) [15,18]. More recently, Schipper et al suggested that tonic GABA A receptors are a potential target for the treatment of TLE [21]. The aim of this study was to determine the molecular mechanism of the antiseizure effects of quercetin on the expression of the GABA A a5 receptor gene in a KA model of epilepsy in mice.…”
Section: Introductionmentioning
confidence: 91%